In Vitro Synergy of Caspofungin and Amphotericin B against Aspergillus and Fusarium spp. - Arikan, Sevtap (American Society for Microbiology, 2002)
We investigated the in vitro interaction of caspofungin and amphotericin B for clinical isolates of Aspergillus and Fusarium. Synergy tests were performed using the checkerboard method and following the NCCLS M38-P guidelines in Antibiotic Medium 3 broth supplemented to 2% glucose. Antagonism was not observed for any of the isolates tested. Caspofungin and amphotericin B were synergistic or synergistic to additive for at least half of the isolates.